The trade effects of the African Continental Free Trade Area: An empirical analysis. (20th December 2022) - Geda, Alemayehu; Yimer, Addis
Abstract: This study examines the possible effects of the African Continental Free Trade Area (AfCFTA) agreement tariff reduction protocol on intra‐African goods trade using two approaches: trade indices and a gravity model. In both approaches, an attempt to identify the trade‐creation and trade‐diversion effects of the proposed AfCFTA is made. The two approaches combined suggest that the AfCFTA could raise intra‐African exports from the average annual value of US 72.7 billion (2015–2017) by about US 13.7 billion (by about 19%). For the success of the AfCFTA, the success in political activism needs to be combined with a continental industrial strategy that includes continental protection for infant industries in tandem with this continental liberalisation.